Ata Durdıyev’in Keymir Kör Tarihi romanı (sayfa 9-54): (metin-çeviri-dizin-gramer incelemesi) - Seyfi, Hacı (My University, 2008)
Çalışma 1995 yılında Türkmen Türkçesiyle yazılmış “Kör Keymir” isimli tarihi romanın 9-54. sayfalar arası esas alınarak hazırlanmıştır. Beş bölümden oluşan çalışmanın “Giriş” bölümünde Türkmen edebiyatı ve yazı dili hakkında kısaca bilgi verilmiştir. “İnceleme” Türkmen Türkçesindeki edatlar çalışmaya konu olan tarihi romandan örnekler alınarak incelenmiştir. Kiril alfabesindeki bu romanın “Metin” bölümünde Türkmen Türklerinin günümüzde kullanmakta oldukları Latin alfabesine çevrilmiştir. “Aktarma” bölümde roman Türkiye Türkçesine aktarılmıştır. “Dizin” bölümünde ise, romanda geçen bütün kelimeler Latin Alfabesine göre sıralanmıştır. Çalışmanın Türkmen Türkçesinin mevcut sorunlarından bir kısmına ışık tutabilmesi ve bu sahadaki ihtiyaca belli ölçülerde cevap verebilmesi umulmaktadır.

The study was written in 1995 in Aşgabat(a city in Turkmenistan) in Turkoman Turkish, and it was based on a historical novel called “Keymir Kör” written by famous writer Ata Durdıyev. In the “Introduction” section of the study, which consists of five sections, a brief information on Turkoman Literature and literary language has been given. In the “Research” section, the particles in Turkoman Turkish have been examined by taking examples from the historical novel which has been the subject matter of the study. In the “Text” section of the historical novel written in Cyrillic alphabet, it has been translated into Latin alphabet which Turkomans use at the present time. In the “Transposition” section, the historical novel has been transferred into Turkish used in Turkey. Moreover, in the “Index” section all the words taking part in the historical novel are listed in alphabetical order according to Latin alphabet . The study is expected to shed light on some of the extant problems in Turkoman Turkish and to meet the need to some extent in this field .
Keywords: Roman; Türk Dili